Trauma, Resilience, and Health Promotion in LGBT Patients : What Every Healthcare Provider Should Know - Eckstrand, Kristen L.; Potter, Jennifer (Springer International Publishing : Imprint: Springer, 2017)
This book has two goals: to educate healthcare professionals about the effect of identity-based adversity on the health of their LGBT patients, and to outline how providers can use the clinical encounter to promote LGBT patients' resilience in the face of adversity and thereby facilitate recovery. Toward this end, it addresses trauma in LGBT populations; factors that contribute to resilience both across the lifespan and in specific groups; and strategies for promoting resilience in clinical practice. Each chapter includes a case scenario with discussion questions and practice points that highlight critical clinical best practices. The editors and contributors are respected experts on the health of LGBT people, and the book will be a "first of its kind" resource for all clinicians who wish to become better educated about, and provide high quality healthcare to, their LGBT patients.
Keywords: Medicine.; General practice (Medicine).; Primary care (Medicine).; Psychotherapy.; elektronické knihy; electronic books